ARTIFICIAL INTELIGENCE IN THE FIELD OF EDUCATION THAT INFLUENCES HOW VALUES AND CHARACTER ARE FORMED AT STATE VOCATIONAL HIGH SCHOOL (SMKN 1) TAPAKTUAN, SOUTH ACEH REGENCY - Anhar; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Artificial intelligence and character development in the field of education. Asubfield of computer science called artificial intelligence is focused on thecreation of artificial intelligence, thought patterns, and human-like behavior.Voice recognition, problem-solving, education, and planning are a fewexamples. The growth of intellect is significantly influenced by artificialintelligence (AI), a subset of the digital literacy system. The use of ai is one ofthe innovative efforts in learning media that are required in the field ofeducation. This study aims to enhance student learning while fostering moralsand virtues and assisting ai systems in their adaptation. The approach adoptedemploys experimental techniques to ascertain how student reactions andadaption.